Transgenerational effect of prenatal stress on behavior and lipid peroxidation in brain structures of female rats during the estral cycle - A. V. Vyushina; A. V. Pritvorova; S. G. Pivina; N. E. Ordyan (Вавиловский журнал генетики и селекции)
The effect of stress in pregnant female Wistar rats on the behavior and lipid peroxidation (LP) in the neocortex, hippocampus and hypothalamus in the female F2 generation during the ovarian cycle was investigated. We subjected pregnant females to daily 1-hour immobilization stress from the 15th to the 19th days of pregnancy. Further, family groups were formed from prenatally stressed and control male and female rats of the F1 generation: group 1, the control female and male; group 2, the control female and the prenatally stressed male; group 3, the prenatally stressed female and the control male; group 4, the prenatally stressed female and male. The females of the F2 generation born from these couples were selected into four experimental groups in accordance with the family group. At the age of 3 months, behavior of rats was studied in the “open field” test in two stages of the ovarian cycle – estrus and diestrus. After 7–10 days, the rats were decapitated and the neocortex, hypothalamus and hippocampus were selected to determine the level of diene and triene conjugates, Schiff bases and the degree of lipid oxidation (Klein index). In F2 females with one prenatally stressed parent, there was no interstage difference in locomotorexploratory activity and anxiety. If both F1 parents were prenatally stressed, female F2 rats retained interstage differences similar to the control pattern, while their locomotor-exploratory activity and time spent in the center of an “open field” decreased in absolute values. In the neocortex of F2 females in groups with prenatally stressed mothers, the level of primary LP products decreased and the level of Schiff bases increased in the estrus stage. In the hippocampus of F2 females in the groups with prenatally stressed fathers, the level of Schiff bases decreased in the estrus stage, and the level of primary LP products increased in group 2 and decreased in group 4. In the hypothalamus of F2 females in the groups with prenatally stressed mothers, the level of Schiff bases increased in the estrus stage and decreased in the diestrus; in addition, in group 3, the level of primary LP products in the estrus stage increased. Thus, we demonstrated the influence of prenatal stress of both F1 mother and F1 father on the behavior and the level of LP in the neocortex, hippocampus and hypothalamus in female rats of the F2 generation in estrus and diestrus.